(untitled) (Research, Society and Development, 2023)
Objective: To describe the clinical and perinatal outcomes of unvaccinated pregnant women with Covid-19 who underwent cesarean delivery in a reference maternity hospital in southern Brazil, and compare them with those of unvaccinated pregnant women with similar characteristics, without Covid-19 infection. 19. Methods: This was a retrospective cohort study, carried out between December 2021 and August 2022. The studied population consisted of pregnant women with Covid-19 who were not immunized with the vaccine against Covid-19 (n=91), compared to a control group of unvaccinated pregnant women without evidence of previous or current infection with Covid-19 (n= 57). The tests used for statistical analysis were: t test for unpaired independent samples, Mann-Whitney test, chi-square test and two-tailed Fisher’s exact test with Freeman-Halton extension. As outcomes, ICU admission and deaths of pregnant women and newborns in both groups were investigated. Results: there was a greater tendency towards ICU admission and death in pregnant women with Covid-19 (RR= 9.4; 95% CI: 0.55 – 162.5) and (RR = 3.15; 95% CI: 0.15 – 64.50), respectively. Newborns had a higher risk of admission to the Neonatal ICU (RR = 1.73; 95% CI: 0.73 – 4.14) and a greater chance of death (RR = 2.45, 95% CI: 0.28 – 21.40). Conclusions: pregnant women with Covid-19 and their newborns had a higher risk of hospitalization in the ICU/Neonatal ICU and a higher risk of death.